Characterization of a New Saccharomyces cerevisiae Isolated From Hibiscus Flower and Its Mutant With L-Leucine Accumulation for Awamori Brewing - Abe, Takayuki; Toyokawa, Yoichi; Sugimoto, Yukiko; Azuma, Haruna; Tsukahara, Keiko; Nasuno, Ryo; Watanabe, Daisuke; Tsukahara, Masatoshi; Takagi, Hiroshi (Frontiers in Genetics, 2019)
Since flavors of alcoholic beverages produced in fermentation process are affected mainly by yeast metabolism, the isolation and breeding of yeasts have contributed to the alcoholic beverage industry. To produce awamori, a traditional spirit (distilled alcoholic beverage) with unique flavors made from steamed rice in Okinawa, Japan, it is necessary to optimize yeast strains for a diversity of tastes and flavors with established qualities. Two categories of flavors are characteristic of awamori; initial scented fruity flavors and sweet flavors that arise with aging. Here we isolated a novel strain of Saccharomyces cerevisiae from hibiscus flowers in Okinawa, HC02-5-2, that produces high levels of alcohol. The whole-genome information revealed that strain HC02-5-2 is contiguous to wine yeast strains in a phylogenic tree. This strain also exhibited a high productivity of 4-vinyl guaiacol (4-VG), which is a precursor of vanillin known as a key flavor of aged awamori. Although conventional awamori yeast strain 101-18, which possesses the FDC1 pseudogene does not produce 4-VG, strain HC02-5-2, which has the intact PAD1 and FDC1 genes, has an advantage for use in a novel kind of awamori. To increase the contents of initial scented fruity flavors, such as isoamyl alcohol and isoamyl acetate, we attempted to breed strain HC02-5-2 targeting the L-leucine synthetic pathway by conventional mutagenesis. In mutant strain T25 with L-leucine accumulation, we found a hetero allelic mutation in the LEU4 gene encoding the Gly516Ser variant α-isopropylmalate synthase (IPMS). IPMS activity of the Gly516Ser variant was less sensitive to feedback inhibition by L-leucine, leading to intracellular L-leucine accumulation. In a laboratory-scale test, awamori brewed with strain T25 showed higher concentrations of isoamyl alcohol and isoamyl acetate than that brewed with strain HC02-5-2. Such a combinatorial approach to yeast isolation, with whole-genome analysis and metabolism-focused breeding, has the potentials to vary the quality of alcoholic beverages.